2019
DOI: 10.1177/0959683619875804
|View full text |Cite
|
Sign up to set email alerts
|

Relating dung fungal spore influx rates to animal density in a temperate environment: Implications for palaeoecological studies

Abstract: The management of the remainder of Europe’s once extensive forests is hampered by a poor understanding of the character of the vegetation and drivers of change before the onset of clearance for farming. Pollen data indicate a closed-canopy, mixed-deciduous forest, contrasting with the assertion that large herbivores would have maintained a mosaic of open grassland, regenerating scrub and forested groves. Coprophilous fungal spores from sedimentary sequences are increasingly used as a proxy for past herbivore i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 94 publications
(188 reference statements)
0
23
0
Order By: Relevance
“…Therefore, including other dung fungal spores such as Sordaria appears to be an effective additional measure to minimise the uncertainty associated with Sporormiella zero counts. Besides megaherbivore abundance, other factors affect spore abundance (van Asperen et al, 2019). These factors include (1) moisture availability for fungal growth and hydrology (Wood and Wilmshurst, 2011), (2) shoreline morphology, (3) seasonality of climate and wind impacting fungal growth and dispersal (van Asperen, 2017), (4) taphonomic effects including the sedimentary environment and spore preservation, and (5) laboratory procedures (van Asperen et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, including other dung fungal spores such as Sordaria appears to be an effective additional measure to minimise the uncertainty associated with Sporormiella zero counts. Besides megaherbivore abundance, other factors affect spore abundance (van Asperen et al, 2019). These factors include (1) moisture availability for fungal growth and hydrology (Wood and Wilmshurst, 2011), (2) shoreline morphology, (3) seasonality of climate and wind impacting fungal growth and dispersal (van Asperen, 2017), (4) taphonomic effects including the sedimentary environment and spore preservation, and (5) laboratory procedures (van Asperen et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…When herbivores engage in coprophagy, they simultaneously consume the fungal fruitbodies (with spores inside) that grow on the surface of faeces, and plant material with attached spores [14,20]. The spores have thick melanised walls that act as protective layers, allowing them to travel through the digestive system without being harmed [16,32]; the thick wall also improves the likelihood of SCF being preserved in sedimentary records [35]. Having passed through the digestive track of an animal, ultimately dung and the incorporated spores will then be ejected and the spores are left to germinate and grow on the dung substrate [16,19,32,35].…”
Section: Figure 1 the Endocoprophilous Life Cycle Of Coprophilous Fungimentioning
confidence: 99%
“…The spores have thick melanised walls that act as protective layers, allowing them to travel through the digestive system without being harmed [16,32]; the thick wall also improves the likelihood of SCF being preserved in sedimentary records [35]. Having passed through the digestive track of an animal, ultimately dung and the incorporated spores will then be ejected and the spores are left to germinate and grow on the dung substrate [16,19,32,35]. At a mature stage of fructification, the fungi eject spores away from the dung onto the surrounding herbage for the cycle to repeat itself [13,14,16].…”
Section: Figure 1 the Endocoprophilous Life Cycle Of Coprophilous Fungimentioning
confidence: 99%
“…Increase in spores of coprophilous fungi Abundant fungal spores (e.g., Sordaria, Sporormiella, Gelasinospora) commonly associated with dung were recovered in sediment pollen archives in the Savanna, Grasslands and IOCB Biomes, possibly indicating the presence of pastoralism across South Africa, Botswana, and Mozambique beginning as early as 2000-1500 BP (Neumann et al, 2014;Ekblom et al, 2014b;Cordova et al, 2017;Hahn et al, 2021). Palaeoecological studies focused on dung fungal spores have shown that their presence is often associated with the dung of herbivores (Cugny et al, 2010;Baker et al, 2013;Cheruiyot et al, 2020;van Asperen et al, 2020), though some fungal taxa (e.g., Gelasinospora) grow rapidly on other substrates (Cheruiyot et al, 2020;van Asperen et al, 2020). Thus, a significant increase in dung fungal spores is a potential indicator of grazing particularly during known periods of pastoralism in the archaeological record especially if spores of coprophilous fungi co-occur with e.g., pollen of crops and weeds.…”
Section: Large Poaceae Pollen (> 40 µM)mentioning
confidence: 99%